Mechanical site preparation treatment and species effects on carbon pools in 12-year-old American sycamore [Platanus occidentalis L.] and willow oak [Quercus phellos L.] riparian plantations, Virginia Piedmont, USA - Drake H. Lynn; W. Michael Aust; David R. Carter; P. Corey Green; John R. Seiler (New Forests, 2025)
Restoration of riparian forests can improve water quality and wildlife habitat and also sequester carbon. Unfortunately, failures of riparian restoration efforts are common due to planting mortality. Selection of well-suited species, dense planting and use of mechanical soil site preparations may potentially enhance wetland restoration plantings. Carbon valuation of forestland is increasing and additional research is needed to determine rates and pools of carbon accumulation in riparian areas. We evaluated the effects of four soil mechanical site preparation treatments (bedding, disking, pit and mounding, and ripping) and species selection (American sycamore [ Platanus occidentalis L.] and willow oak, [ Quercus phellos L.] on survival, growth and carbon storage across multiple pools: planted trees, herbaceous vegetation, fine roots, organic soil (litter) horizons, and the mineral soil. At 12 years, species selection was more important to carbon storage than site preparation. American sycamore was well-suited to the site and had better survival than willow oak (64% vs. 42% survival). American sycamore also stored more carbon across all site preparation methods than willow oak. Measured carbon storage averaged 74.8 Mg ha −1 for American sycamore treatments and 63.1 Mg ha −1 for willow oak treatments. The densely planted treatments established forests even in higher mortality willow oak plots. Results indicate that appropriate species planted at high densities may be used to enhance forest stand establishment and carbon storage in similar riparian restorations.